PENERAPAN SOCIAL MEDIA MARKETING DI ERA DIGITAL UNTUK KEMAJUAN UMKM DISABILITAS DI KOTA PADANG - Dessy Kurnia Sari; Donard Games; venny darlis; Laura Amelia Triani; muhammad ikhsan syahputra (Jurnal Hilirisasi IPTEKS, 2024)
The Digital Age requires novelty in the way of doing business. For business people, increasing knowledge about social media marketing is a must. MSMEs need to be more responsive and aware of how to display products that are attractive to consumers. Thus, this activity aims to improve social media marketing capabilities for MSMEs with disabilities who are constrained by access to information and product socialization to consumers. This social media marketing training was carried out by a team of lecturers at the Faculty of Economics and Business, Universitas Andalas, by involving several content creators in Padang City. The method of implementing the activity involves twenty-five MSME actors with disabilities who are members of Karajoelok.com and special needs students in Padang City. The training includes taking attractive product photos and creating product advertisements on social media. Participants in the activity were accompanied in the process of taking pictures and displaying them on social media. The activity results include improving the ability of people with disabilities who are members of karajoelok.com, a platform for marketing products for disabled MSMEs, how to produce the best photos of their products. After the training, the products of business actors with disabilities can be better known by the community (building awareness) to create economic independence for MSME actors with disabilities, especially those who are partners of karajoelok.com. This activity shows that everyone can make something enjoyable if they are serious about doing it, including MSME actors with disabilities. With the increase in social media marketing capabilities, the digital era does not need to be feared because it opens up opportunities for local products to be more accepted by the market.